Neurofilament as a blood marker for diagnosis and monitoring of primary progressive aphasias. (7th March 2017) - Steinacker, Petra; Semler, Elisa; Anderl-Straub, Sarah; Diehl-Schmid, Janine; Schroeter, Matthias L.; Uttner, Ingo; Foerstl, Hans; Landwehrmeyer, Bernhard; von Arnim, Christine A.F.; Kassubek, Jan; Oeckl, Patrick; Huppertz, Hans-Jürgen; et al.
Abstract : Objective: To assess the utility of serum neurofilament for diagnosis and monitoring of primary progressive aphasia (PPA) variants. Methods: We investigated neurofilament light chain (NF-L) levels in blood of 99 patients with PPA (40 with nonfluent variant PPA [nfvPPA], 38 with semantic variant PPA [svPPA], 21 with logopenic variant PPA [lvPPA]) and compared diagnostic performance with that reached by CSF NF-L, phosphorylated neurofilament heavy chain (pNF-H), β-amyloid (Aβ1-42 ), tau, and phosphorylated tau. The longitudinal change of blood NF-L levels was measured and analyzed for correlation with functional decline and brain atrophy. Results: Serum NF-L is increased in PPA compared to controls and discriminates between nfvPPA/svPPA and lvPPA with 81% sensitivity and 67% specificity (cutoff 31 pg/mL). CSF NF-L, pNF-H, tau, phosphorylated tau, and Aβ1-42 achieved similar performance, and pNF-H was the only marker for discrimination of nfvPPA from svPPA/lvPPA. In most patients with nfvPPA and svPPA, but not lvPPA, serum NF-L increased within follow-up. The increase correlated with functional decline and progression of atrophy of the left frontal lobe of all patients with PPAs and the right middle frontal gyrus of patients with nfvPPA and svPPA. Conclusions: Blood level of NF-L can aid the differential diagnosis of PPA variants, especially in combination with CSF pNF-H. Because serum NF-L correlates with functional decline and atrophy in the disease course, it qualifies as an objective disease status marker. Extended follow-up studies with cases of known neuropathology are imperative. Classification of evidence: This study provides Class I evidence that in patients with PPA, blood levels of NF-L can distinguish the logopenic variant from the nonfluent/agrammatic and semantic variants.